EMOTION FOCUSED COPING DALAM MENANGANI KEJENUHAN WARGA BINAAN PEMASYARAKATAN WANITA DI RUTAN KELAS IIB BOYOLALI - Amanda Safitri; Alfin Miftahul Khairi (Universitas Muhammadiyah Metro, 2025)
This study employs a qualitative research design with a case study approach. The research subjects were selected using purposive sampling and comprised four female inmates of a corretional facility. Data were collected through observation and interviews. Data analysis followed Miles and Huberman interactive model, conducted continuously until completion to ensure validity. The credibility of the data was ensured through source triangulation and technique triangulation. The findings revealed that emotion focused coping involved social support, such as fulfilling needs, visits, and telephone services. Positive interpretation was evidenced by joint and individual activities, self acceptance following the verdict, and the absence of rejection, facilitated by social and religious support. These findings suggest the effectiveness of emotion focused coping trategies in managing boredom of female inmates.